Composite plasticizer, silicon nitride green body, preparation method of silicon nitride green body and silicon nitride ceramic chip
By using composite plasticizers in the production of silicon nitride ceramic sheets, the potential risks of plasticizers to the environment and health in the prior art and the deformation and 'oil output' defects caused by small-molecular plasticizers are solved, and safer and more efficient plasticizers and product quality are achieved.
Patent Information
- Application Number
- CN202411182310.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-04-08
AI Technical Summary
Phthalate plasticizers used in the production of existing silicon nitride ceramic sheets have potential risks to the environment and human health, and their substitutes such as small-molecular plasticizers are prone to deformation of silicon nitride green bodies and ‘oil output’ defects.
Compound plasticizers, including high molecular weight diol polymers and low molecular weight second plasticizers, are adopted to inhibit the regular arrangement of the binder molecular chains through their unique molecular structure and interactions, reduce the glass transition temperature, and limit the migration of the second plasticizer to the surface of the silicon nitride slurry, reducing the 'oil output' defects.
It effectively replaces phthalate plasticizers, reduces environmental and health risks, and improves the plasticization effect and product yield of silicon nitride ceramic sheets, avoiding the defect of "oil output".
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ceramic materials, and in particular to a composite plasticizer, a silicon nitride green body and a preparation method thereof, and a silicon nitride ceramic sheet. Background Art
[0002] Silicon nitride ceramic sheets are a new type of semiconductor ceramic material with the advantages of high thermal conductivity, high mechanical strength, and high resistivity. They can be used to make ceramic copper-clad substrates for chip packaging, giving the substrates characteristics such as low dielectric constant, insulation, high thermal conductivity, high strength, and good chemical stability.
[0003] At present, silicon nitride ceramic sheets are usually produced by tape casting. That is, silicon nitride powder is made into slurry, tape-casted to form silicon nitride tape-cast green body, and then high-temperature debinding sintering is performed to obtain the finished silicon nitride ceramic sheet. In order to ensure the mechanical toughness and appearance integrity of the silicon nitride tape-cast green body, a plasticizer component, such as dimethyl phthalate, needs to be added to the slurry formula.
[0004] As the most widely used plasticizer, dimethyl phthalate is widely used in industries such as food processing and packaging, flooring manufacturing and automobile production. However, as incidents of harm to human health and the environment caused by phthalates continue to be reported, restrictions on the use of such substances will begin. Although the sintering manufacturing process temperature of silicon nitride ceramic sheets reaches above 1500°C, which can completely decompose dimethyl phthalate, it is still unavoidable to contact with phthalates during the contact process with silicon nitride tape casting green body and the debinding and degreasing operation, thus generating potential environmental and health risks. Summary of the invention
[0005] The embodiments of the present application provide a composite plasticizer, silicon nitride slurry and silicon nitride ceramic sheet, which can replace phthalate plasticizers, ensure the plasticizing effect while reducing environmental and health risks.
[0006] In order to achieve the above-mentioned object, according to a first aspect of the present application, a composite plasticizer is provided, comprising a first plasticizer and a second plasticizer;
[0007] The first plasticizer includes at least one of a glycol polymer and a glycol polymer monomethyl ether; the molecular formula of the glycol polymer is HO-(C a H 2a O) b -H, the molecular formula of glycol polymer monomethyl ether is HO-(C a H 2a O) b -CH3, 2≤a≤6, and the molecular weight of the glycol polymer and the glycol polymer monomethyl ether is 2000-10000;
[0008] The molecular formula of the second plasticizer is R1-(C m H 2m O) n -R2, 2≤m≤6, 2≤m*n≤30, R1 is one of hydroxyl, alkoxy or carboxylate, and R2 is one of hydrogen, alkyl or alkylcarbonyl.
[0009] Optionally, the mass ratio of the first plasticizer to the second plasticizer is 1:(1-2).
[0010] According to a second aspect of the present application, a silicon nitride green body is further provided, wherein the raw materials of the silicon nitride green body include the above composite plasticizer.
[0011] Optionally, the raw materials of the silicon nitride green body include the following components in parts by weight: 40-55 parts of silicon nitride powder, 1-4 parts of sintering aid, 0.5-3 parts of dispersant, 4-8 parts of binder, 2.5-10 parts of composite plasticizer, 30-40 parts of solvent and 0.2-1 part of defoamer.
[0012] Optionally, the binder includes polyvinyl butyral of different molecular weights, the weight average molecular weight of the polyvinyl butyral is 50,000-200,000, and the mass proportion of hydroxyl groups in the polyvinyl butyral is 17%-23%.
[0013] Optionally, the solvent includes ethanol and ethyl acetate, and the mass ratio of ethanol to ethyl acetate is 4:6 to 7:3.
[0014] Optionally, the mass proportion of α phase in the silicon nitride powder is greater than 90%, the particle size D50 is less than 1 μm, and the specific surface area is 10-20 m 2 / g.
[0015] Optionally, the sintering aid includes at least one of magnesium oxide and yttrium oxide.
[0016] Optionally, the dispersant includes at least one of polyvinyl pyrrolidone, triethyl phosphate and castor oil.
[0017] According to a third aspect of the present application, a method for preparing a silicon nitride green body is also provided, which is used to prepare the silicon nitride green body as above, comprising:
[0018] Mixing raw materials of silicon nitride green bodies to obtain silicon nitride slurry;
[0019] The silicon nitride slurry is tape-cast to obtain a silicon nitride green body.
[0020] Optionally, raw materials of silicon nitride green bodies are mixed to obtain silicon nitride slurry, including:
[0021] Mixing silicon nitride powder, a dispersant, a sintering aid and a portion of a solvent according to a proportion to obtain a first slurry;
[0022] Mixing the binder, the composite plasticizer, the defoamer and another portion of the solvent according to a certain proportion to obtain a second slurry;
[0023] The first slurry and the second slurry are mixed to obtain silicon nitride slurry.
[0024] According to a fourth aspect of the present application, there is also provided a silicon nitride ceramic sheet, which is prepared from the above silicon nitride green body, or prepared by the above method for preparing the silicon nitride green body.
[0025] The composite plasticizer of the embodiment of the present application comprises a first plasticizer and a second plasticizer. The first plasticizer comprises at least one of a glycol polymer and a glycol polymer monomethyl ether, and the molecular formula of the glycol polymer is HO-(C a H 2a O) b -H, the molecular formula of glycol polymer monomethyl ether is HO-(C a H 2a O) b -CH3, 2≤a≤6, and the molecular weight of the glycol polymer and the glycol polymer monomethyl ether is 2000-10000. The molecular formula of the second plasticizer is R1-(C m H 2m O) n -R2, 2≤m≤6, 2≤m*n≤30, R1 is one of hydroxyl, alkoxy or carboxylate, and R2 is one of hydrogen, alkyl or alkylcarbonyl. That is, the composite plasticizer includes a first plasticizer with a high molecular weight and a second plasticizer with a low molecular weight. When the composite plasticizer is applied to silicon nitride slurry, the second plasticizer with a low molecular weight has a strong ability to move and migrate, which can inhibit the regular arrangement of the molecular chains of the binder in the silicon nitride slurry and reduce the glass transition temperature. The molecular chains of the first plasticizer with a high molecular weight can be entangled with the binder in the silicon nitride slurry, thereby reducing the crystallization trend, and the first plasticizer with a high molecular weight can interact with the second plasticizer with a low molecular weight to limit the tendency of the second plasticizer to migrate to the surface of the silicon nitride slurry, reducing the probability of the occurrence of "oiling" defects in the later blank. The embodiment of the present application can replace the phthalate plasticizer in the related art through the composite plasticizer, while improving the plasticizing effect, reducing environmental and health risks.
[0026] Other features and advantages of the present application will be described in detail in the subsequent detailed description. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0028] In the related art, in order to replace phthalate plasticizers, small molecule plasticizers similar to phthalate substances are usually selected, such as propylene glycol, etc. However, such small molecule plasticizers have strong water absorption capacity, which can easily cause defects such as deformation of silicon nitride green bodies. In addition, small molecule plasticizers have strong migration and mobility, and can easily migrate to the surface of silicon nitride green bodies, thereby causing "oiling" problems, which in turn cause adhesion between silicon nitride green bodies, resulting in a decrease in product yield.
[0029] The present application provides a composite plasticizer. The composite plasticizer of the present application embodiment includes a first plasticizer and a second plasticizer. The first plasticizer includes at least one of a glycol polymer and a glycol polymer monomethyl ether; the molecular formula of the glycol polymer is HO-(C a H 2a O) b -H, the molecular formula of glycol polymer monomethyl ether is HO-(C a H 2a O) b -CH3, 2≤a≤6, and the molecular weight of the glycol polymer and the glycol polymer monomethyl ether is 2000-10000. The molecular formula of the second plasticizer is R1-(C m H 2m O) n -R2, 2≤m≤6, 2≤m*n≤30, R1 is one of hydroxyl, alkoxy or carboxylate, and R2 is one of hydrogen, alkyl or alkylcarbonyl. That is, the composite plasticizer includes a first plasticizer with a high molecular weight and a second plasticizer with a low molecular weight. When the composite plasticizer is applied to silicon nitride slurry, the second plasticizer with a low molecular weight has a strong ability to move and migrate, which can inhibit the regular arrangement of the molecular chains of the binder in the silicon nitride slurry and reduce the glass transition temperature. The molecular chains of the first plasticizer with a high molecular weight can be entangled with the binder in the silicon nitride slurry, thereby reducing the crystallization trend, and the first plasticizer with a high molecular weight can interact with the second plasticizer with a low molecular weight to limit the tendency of the second plasticizer to migrate to the surface of the silicon nitride slurry, reducing the probability of the occurrence of "oiling" defects in the later blank. The embodiment of the present application can replace the phthalate plasticizer in the related art through the composite plasticizer, while improving the plasticizing effect, reducing environmental and health risks.
[0030] The value range of a in the first plasticizer is 2≤a≤6, and the value range of m in the second plasticizer is 2≤m≤6. When the value ranges of a and m meet the above conditions, it can ensure that the molecules of the first plasticizer and the second plasticizer have moderate polarity and good solubility in the selected solvent system to achieve a plasticizing effect.
[0031] In the molecular formulas of the first plasticizer and the second plasticizer, the values of a, b, m and n are all integers.
[0032] For example, the first plasticizer may be PEG4000 (polyethylene glycol with an average molecular weight of 4000), PEG6000 (polyethylene glycol with an average molecular weight of 6000), PPG4000 (polypropylene glycol with an average molecular weight of 4000) or PPG6000 (polypropylene glycol with an average molecular weight of 6000). The second plasticizer may be PEG600 (polyethylene glycol with an average molecular weight of 600), triethylene glycol di-n-butyl ester, PEPG6500 (polyethylene propylene glycol with an average molecular weight of 6500) or dipropylene glycol di-n-butyl ester.
[0033] It can be understood that the above exemplary description is only to provide examples of the first plasticizer and the second plasticizer, and is not intended to limit the scope of the first plasticizer and the second plasticizer in the present application.
[0034] In some embodiments, the mass ratio of the first plasticizer to the second plasticizer is 1:(1-2). The molecular weight of the first plasticizer is high, and it has good heat resistance, migration resistance and stability, while the low molecular weight second plasticizer has better solubility and plasticizing efficiency. By mixing the two in a certain proportion, their respective advantages can be better utilized to improve the overall performance. If the proportion of the first plasticizer is too high, it is easy to cause poor plasticizing effect, and if the proportion of the second plasticizer is too high, it is easy to cause poor stability and easy to produce the defect of "oiling" of the blank.
[0035] According to the second aspect of the present application, an embodiment of the present application further provides a silicon nitride green body, and the raw materials of the silicon nitride green body include the above composite plasticizer.
[0036] By applying the above-mentioned composite plasticizer to the silicon nitride green body, the phthalate plasticizer in the conventional technology can be substituted, and the environmental and health risks are reduced. Since the plasticizer includes a first plasticizer of high molecular weight and a second plasticizer of low molecular weight at the same time, it has better comprehensive performance. Specifically, the second plasticizer of low molecular weight has a strong ability to move and migrate, which can suppress the regular arrangement of the molecular chains of the binder in the silicon nitride slurry and reduce the glass transition temperature. The molecular chains of the first plasticizer of high molecular weight can be entangled with the binder in the silicon nitride slurry, thereby reducing the crystallization trend, and the first plasticizer of high molecular weight can interact with the second plasticizer of low molecular weight to limit the trend of the second plasticizer to migrate to the surface of the silicon nitride slurry, reducing the probability of the occurrence of the "oiling" defect of the late blank. Therefore, in the embodiment of the present application, the silicon nitride green body, by adopting the above-mentioned composite plasticizer, while reducing the environmental and health risks, ensures the plasticizing performance and improves the yield of the product.
[0037] In some embodiments, the raw materials of silicon nitride green body include the following components by weight: 40-55 parts of silicon nitride powder, 1-4 parts of sintering aid, 0.5-3 parts of dispersant, 4-8 parts of binder, 2.5-10 parts of composite plasticizer, 30-40 parts of solvent and 0.2-1 parts of defoaming agent.
[0038] The amount of solvent added is controlled at 30-40 parts, which can make the slurry made from the raw materials have a suitable viscosity, reduce the difficulty of forming the silicon nitride green body, and also reduce the surface defects of the silicon nitride green body caused by solvent volatilization during the subsequent drying process.
[0039] In some embodiments, the binder includes polyvinyl butyral (PVB) of different molecular weights, the weight average molecular weight of the polyvinyl butyral is 50000-200000, and the mass proportion of hydroxyl groups in the polyvinyl butyral is 17%-23%. By compounding polyvinyl butyrals of different molecular weights as a binder, the silicon nitride slurry prepared from the raw materials of the silicon nitride green body can have higher stability and can reduce the risk of cracking during the debinding process.
[0040] It can be understood that the binder comprising polyvinyl butyral of different molecular weights means that the binder comprises at least two polyvinyl butyrals of weight average molecular weights, for example, the binder comprises polyvinyl butyral of weight average molecular weight of 50,000 and polyvinyl butyral of weight average molecular weight of 200,000.
[0041] In some embodiments, the solvent includes ethanol and ethyl acetate, and the mass ratio of ethanol to ethyl acetate is 4:6 to 7:3. The solvent needs to have sufficient solubility for the binder and the composite plasticizer, so as to be able to adjust the viscosity of the slurry. The composite solvent composed of ethanol and ethyl acetate is more environmentally friendly and has lower cost than the benzene or ketone solvents used in the related art. In addition, the boiling point difference between ethanol and ethyl acetate is large, and there is a gradient volatilization in the silicon nitride green body manufacturing process, which can better control the volatilization rate of the solvent, thereby reducing or avoiding cracking defects in the surface layer of the silicon nitride green body caused by too fast solvent volatilization.
[0042] Illustratively, the mass ratio of ethanol to ethyl acetate may be 4:6, 5:5, 6:4 or 7:3.
[0043] In some embodiments, the mass proportion of the α phase in the silicon nitride powder is greater than 90%, the particle size D50 is less than 1 μm, and the specific surface area is 10-20 m 2 / g. The α phase of silicon nitride powder has a higher density at high temperature. Controlling the mass proportion of the α phase in silicon nitride powder to a range greater than 90% facilitates the formation of a denser ceramic material, thereby improving the overall density and strength. Controlling the particle size D50 of silicon nitride powder to below 1μm can make the silicon nitride powder have better fluidity and dispersibility, making the silicon nitride powder more evenly distributed in the slurry. The specific surface area of silicon nitride powder is 10-20m 2 / g, has more surface active sites, so it can better combine with other materials and improve the overall performance.
[0044] In order to improve the performance of silicon nitride powder, silicon nitride powder also meets the following conditions: heteroatom (Fe, Al, Ca) content <300ppm, C atom content <0.1wt%, oxygen content <1wt%. The low content of heteroatoms such as iron (Fe), aluminum (Al) and calcium (Ca) in silicon nitride powder helps to reduce the precipitation and phase change of impurities in the silicon nitride green body during sintering, reduce the adverse effects on material properties, and low heteroatom content can also improve the electrical insulation and chemical stability of the material. The carbon (C) atom content is less than 0.1wt%, which helps to avoid the formation of carbon deposition during the sintering of the silicon nitride green body and maintain the purity and uniformity of the material. The oxygen content is less than 1wt%, which can reduce the formation of oxides, promote the densification of silicon nitride powder, and improve mechanical properties.
[0045] In some embodiments, the sintering aid includes at least one of magnesium oxide and yttrium oxide. Magnesium oxide can form a liquid phase at a relatively low temperature, promote the rearrangement and densification of materials in the silicon nitride green body, reduce the sintering temperature, and thus improve production efficiency. Magnesium oxide can also contribute to densification, improve microstructure and other effects, and it has excellent high temperature stability, can remain stable during high temperature sintering, and is not easy to volatilize or decompose. Yttrium oxide can also form a liquid phase during the sintering process, promote the rearrangement and densification of materials in the silicon nitride green body, and improve density.
[0046] Furthermore, the purity of magnesium oxide and yttrium oxide is greater than 99.5%, the particle size D50 is less than 2 μm, the heteroatom (Fe, Al, Ca) content is less than 300 ppm; and the moisture content is less than 0.1 wt%. Similar to silicon nitride powder, the sintering aid has a high purity and a low impurity content, which can reduce or avoid the precipitation and phase change of impurities in the silicon nitride green body during the sintering process, thereby ensuring performance. The smaller particle size helps it to be more evenly dispersed in the slurry. The lower moisture content can reduce the bubbles formed by the evaporation of water during the sintering process of the silicon nitride green body, reduce the generation of defects, and can increase the sintering speed, density and mechanical properties.
[0047] In some embodiments, the dispersant includes at least one of polyvinyl pyrrolidone, triethyl phosphate and castor oil. The dispersant helps prevent the material from agglomerating in the slurry system, thereby improving the overall uniformity. Polyvinyl pyrrolidone, triethyl phosphate and castor oil all have excellent dispersibility. Among them, polyvinyl pyrrolidone helps to form a dense protective film on the surface of the material to prevent the agglomeration of the material particles, and it can reduce the surface tension of the material particles. Triethyl phosphate has good solubility in an organic solvent system and has high thermal stability. Castor oil is natural and environmentally friendly and has a wide range of applications.
[0048] According to a third aspect of the present application, a method for preparing a silicon nitride green body is also provided, which is used to prepare the silicon nitride green body as above, comprising:
[0049] Mixing raw materials of silicon nitride green bodies to obtain silicon nitride slurry;
[0050] The silicon nitride slurry is tape-cast to obtain a silicon nitride green body.
[0051] The raw materials of silicon nitride green body include the above-mentioned composite plasticizer, which can replace the phthalate plasticizer in conventional technology, reduce environmental and health risks, and reduce the "oiling" defect of silicon nitride green body. The specific effects have been described above and will not be repeated here.
[0052] The equipment required for tape casting is mainly a tape casting machine, which has a simple structure, convenient operation, can achieve continuous production, and has high production efficiency. The silicon nitride green body after tape casting has a uniform texture, and can prepare a large-area, ultra-thin silicon nitride green body, with a high material utilization rate, reducing waste in the production process and saving costs.
[0053] Exemplarily, the silicon nitride slurry is tape-casted, including: after the silicon nitride slurry is subjected to vacuum degassing treatment, it is poured into the casting trough of the tape casting machine, the scraper height is set to 1.0mm-1.5mm, the casting speed is 50mm / min-100mm / min, the drying temperature is 40℃-55℃, and the silicon nitride green body with a thickness of 0.40mm-0.65mm is obtained by tape casting. Through vacuum degassing treatment, bubbles and volatiles in the silicon nitride slurry can be effectively removed, and defects such as cracks and holes caused by bubbles during subsequent molding can be reduced. By setting the scraper height to 1.0mm-1.5mm, a silicon nitride green body with a target thickness of 0.40mm-0.65mm can be obtained. By setting the casting speed to 50mm / min-100mm / min, a high production efficiency can be guaranteed and defects in the production process can be reduced. The drying temperature is set at 40°C-55°C, which can volatilize the solvent in the silicon nitride slurry and avoid thermal stress or damage problems caused by excessive temperature.
[0054] It is understandable that the conditions for silicon nitride tape casting are only exemplary. When preparing silicon nitride green bodies of other target thicknesses, the scraper height and other conditions can be adaptively adjusted according to the target thickness.
[0055] In some embodiments, raw materials of silicon nitride green bodies are mixed to obtain silicon nitride slurry, including:
[0056] Mixing silicon nitride powder, a dispersant, a sintering aid and a portion of a solvent according to a proportion to obtain a first slurry;
[0057] Mixing a binder, a composite plasticizer, a defoamer and another portion of a solvent according to a proportion to obtain a second slurry;
[0058] The first slurry is mixed with the second slurry to obtain silicon nitride slurry.
[0059] That is, in the process of preparing silicon nitride slurry, the binder, composite plasticizer, defoamer and part of the solvent are first made into a second slurry to form a presol, so that the binder and the composite plasticizer are evenly dispersed in the solvent, avoiding problems such as clumping caused by directly mixing all the raw materials, thereby reducing the risk of cracking of the prepared silicon nitride green body and improving the product yield.
[0060] The conditions for mixing silicon nitride powder, dispersant, sintering aid and part of the solvent are set as follows: the mixed raw materials are ball milled for 10-24 hours at a temperature of 25°C and a rotation speed of 200rpm-300rpm to mix the components evenly. The silicon nitride powder, dispersant, sintering aid and part of the solvent can be evenly mixed through the rotation and grinding action of the ball mill to form a stable first slurry, and the particle size of each component can be further refined during the ball milling process.
[0061] The conditions set during the mixing of the binder, composite plasticizer, defoamer and another part of the solvent are: the temperature is 25°C, the mixed raw materials are stirred by a high-speed stirrer, the stirring speed is set to 200rpm-400rpm, and the stirring time is 2h-5h. The binder and composite plasticizer are prone to problems such as agglomeration and core formation during the ball milling process, so the binder, composite plasticizer, defoamer and solvent are first mixed by stirring to uniformly disperse the binder and composite plasticizer in the solvent to form a second slurry in the form of a presol.
[0062] The conditions set during the process of adding the second slurry to the first slurry are as follows: the composite slurry after mixing the first slurry and the second slurry is ball-milled at a temperature of 25°C and a rotation speed of 200rpm-300rpm, and the ball-milling time is 10h-24h. The first slurry and the second slurry are fully mixed by ball milling, and the particle size of the material is further refined during the ball milling process to improve the dispersion performance. Since the binder and the composite plasticizer have been pre-mixed with the defoamer and the solvent to form a presol, it is not easy to have problems such as clumping and core wrapping during the ball milling process, which helps to disperse evenly and reduce the cracking problem of the silicon nitride green body in the later stage.
[0063] According to the fourth aspect of the present application, the present application embodiment also provides a silicon nitride ceramic sheet, which is prepared from the silicon nitride green body as above, or, is prepared by the method for preparing the silicon nitride green body as above. The silicon nitride ceramic sheet provided by the embodiment of the present application has all the effects of the above-mentioned silicon nitride green body or the method for preparing the silicon nitride green body, which will not be repeated here.
[0064] The present application is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.
[0065] Unless otherwise specified, the parts in the embodiments and comparative examples are parts by mass.
[0066] Example 1
[0067] The preparation process of the silicon nitride green body in this embodiment includes:
[0068] (1) 44.5 parts of silicon nitride powder, 1.2 parts of magnesium oxide, 1.8 parts of yttrium oxide, 1 part of triethyl phosphate, 12.5 parts of ethanol and 5 parts of ethyl acetate were ball-milled at 25° C. and 300 rpm for 12 h to prepare a first slurry;
[0069] (2) 7.5 parts of polyvinyl butyral, 3.75 parts of PEG4000 (polyethylene glycol with an average molecular weight of 4000), 3.75 parts of PEG600 (polyethylene glycol with an average molecular weight of 600), 0.5 parts of BYK-1790 defoamer, 13 parts of ethanol and 5.5 parts of ethyl acetate were stirred in a high-speed stirrer at 25° C. and 300 rpm for 2 h to prepare a second slurry;
[0070] (3) adding the second slurry to the first slurry, and ball milling at 300 rpm for 12 h at 25 ° C to obtain silicon nitride slurry;
[0071] (4) After vacuum degassing, the silicon nitride slurry was poured into a casting tank of a casting machine, and the scraper height was set to 1.5 mm, the casting speed was set to 100 mm / min, and the drying temperature was set to 50° C.; thus, a silicon nitride green body was obtained.
[0072] Example 2
[0073] (1) 43 parts of silicon nitride powder, 1.5 parts of magnesium oxide, 1.5 parts of yttrium oxide, 1 part of polyvinyl pyrrolidone, 12.5 parts of ethanol and 7 parts of ethyl acetate were ball-milled at 25° C. and 300 rpm for 12 h to prepare a first slurry;
[0074] (2) 7.5 parts of polyvinyl butyral, 2.5 parts of PEG6000 (polyethylene glycol with an average molecular weight of 6000), 5 parts of triethylene glycol di-n-butyl ester, 0.5 parts of BYK-1790 defoamer, 9 parts of ethanol and 9 parts of ethyl acetate were stirred in a high-speed stirrer at 25° C. and 300 rpm for 2 h to prepare a second slurry;
[0075] (3) adding the second slurry to the first slurry, and ball milling at 300 rpm for 12 h at 25 ° C to obtain silicon nitride slurry;
[0076] (4) After vacuum degassing, the silicon nitride slurry was poured into a casting tank of a casting machine, and the scraper height was set to 1.5 mm, the casting speed was set to 100 mm / min, and the drying temperature was set to 50° C.; thus, a silicon nitride green body was obtained.
[0077] Example 3
[0078] The preparation process of the silicon nitride green body in this embodiment includes:
[0079] (1) 40 parts of silicon nitride powder, 0.5 parts of magnesium oxide, 0.5 parts of yttrium oxide, 3 parts of triethyl phosphate, 15 parts of ethanol and 5 parts of ethyl acetate were ball-milled at 25° C. and 300 rpm for 12 h to prepare a first slurry;
[0080] (2) 8 parts of polyvinyl butyral, 5 parts of PPG4000 (polypropylene glycol with an average molecular weight of 4000), 5 parts of PPG500 (polypropylene glycol with an average molecular weight of 500), 0.2 parts of BYK-1790 defoamer, 13 parts of ethanol and 4.8 parts of ethyl acetate were stirred in a high-speed stirrer at 25° C. and 300 rpm for 2 h to prepare a second slurry;
[0081] (3) adding the second slurry to the first slurry, and ball milling at 300 rpm for 12 h at 25 ° C to obtain silicon nitride slurry;
[0082] (4) After vacuum degassing, the silicon nitride slurry was poured into a casting tank of a casting machine, and the scraper height was set to 1.0 mm, the casting speed was set to 75 mm / min, and the drying temperature was set to 50° C.; thus, a silicon nitride green body was obtained.
[0083] Example 4
[0084] The preparation process of the silicon nitride green body in this embodiment includes:
[0085] (1) 55 parts of silicon nitride powder, 4 parts of magnesium oxide, 0.5 parts of triethyl phosphate, 12 parts of ethanol and 4.5 parts of ethyl acetate were ball-milled at 25° C. and 300 rpm for 12 h to prepare a first slurry;
[0086] (2) 4 parts of polyvinyl butyral, 1 part of PPG6000 (polypropylene glycol with an average molecular weight of 6000), 1.5 parts of dipropylene glycol di-n-butyl ester, 1 part of BYK-1790 defoamer, 12 parts of ethanol and 4.5 parts of ethyl acetate were stirred in a high-speed stirrer at 25° C. and 300 rpm for 2 hours to prepare a second slurry;
[0087] (3) adding the second slurry to the first slurry, and ball milling at 300 rpm for 12 h at 25 ° C to obtain silicon nitride slurry;
[0088] (4) After vacuum degassing, the silicon nitride slurry was poured into a casting tank of a casting machine, and the scraper height was set to 1.5 mm, the casting speed was set to 50 mm / min, and the drying temperature was set to 50° C.; thus, a silicon nitride green body was obtained.
[0089] Comparative Example 1
[0090] The difference between this comparative example and Example 1 is that 3.75 parts of PEG4000 and 3.75 parts of PEG600 in Example 1 are replaced by 7.5 parts of dibutyl phthalate, and the other conditions remain the same as in Example 1.
[0091] Comparative Example 2
[0092] The difference between this comparative example and Example 1 is that 3.75 parts of PEG4000 and 3.75 parts of PEG600 in Example 1 are replaced by 7.5 parts of propylene glycol, and the other conditions remain the same as in Example 1.
[0093] The viscosity, green body thickness and dimensional stability of the silicon nitride slurry in Examples 1-4 and Comparative Examples 1-2 were tested. The viscosity test was based on the viscosity test method in GB / T 10247-2008. The thickness test method was: measuring at any 4 points on the silicon nitride green body and calculating the average value. The dimensional stability test method was: testing the length, width and thickness dimensions once after the silicon nitride green body was prepared, and retesting the length, width and thickness dimensions of the silicon nitride green body after placing it for 7 days, and comparing them. The test results are shown in Table 1:
[0094] Table 1 Comparison of test results of silicon nitride green bodies in different embodiments and comparative examples
[0095]
[0096]
[0097] By comparing Examples 1-4 with Comparative Example 1, it can be found that the composite plasticizer used in Examples 1-4 replaces the dibutyl phthalate in Comparative Example 1, which ensures that the slurry has a higher viscosity, and the obtained silicon nitride green body has a thicker thickness, excellent dimensional stability, and no oiling problem. That is, by replacing the conventional phthalate plasticizer with the composite plasticizer provided in the examples of the present application, the obtained silicon nitride green body can maintain excellent performance, and the slurry viscosity, silicon nitride green body thickness, dimensional stability and appearance are all comparable to those of Comparative Example 1 using a phthalate plasticizer, and because the phthalate plasticizer is replaced by the composite plasticizer, the environmental and safety risks can be significantly reduced.
[0098] By comparing Examples 1-4 and Comparative Example 2, it can be found that: since small molecular weight propylene glycol is used as a plasticizer in Comparative Example 2, the viscosity of the slurry is significantly lower than that of Examples 1-4, resulting in a thinner thickness of the silicon nitride green body prepared under the same conditions, and the silicon nitride green body easily absorbs water during storage, resulting in poor dimensional stability and a more obvious warping problem in appearance. In addition, propylene glycol in Comparative Example 2 easily migrates to the surface, showing a more obvious "oiling" phenomenon, which causes a serious adhesion problem between different silicon nitride green bodies.
[0099] In summary, the composite plasticizer in the embodiment of the present application can replace the phthalate plasticizer, and make the silicon nitride slurry and the silicon nitride green body show the same performance as when the phthalate plasticizer is used, while taking into account the environmentally friendly characteristics and reducing environmental and health risks. And the composite plasticizer provided in the embodiment of the present application guarantees the performance of the silicon nitride green body from multiple aspects compared with the plasticizer with a small molecular weight, and produces a better effect.
[0100] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0101] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0102] The embodiments, implementation methods and related technical features of the present application can be combined and replaced with each other without conflict.
[0103] The above are only preferred embodiments of the present application and do not constitute any form of limitation to the present application. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.
Claims
1. A composite plasticizer, characterized in that including a first plasticizer and a second plasticizer; Wherein, the first plasticizer comprises at least one of a glycol polymer and a glycol polymer monomethyl ether; the molecular formula of the glycol polymer is HO-(C a H 2a O) b -H, the molecular formula of the diol polymer monomethyl ether is HO-(C a H 2a O) b -CH3, 2≤a≤6, and the molecular weight of the diol polymer and the diol polymer monomethyl ether is 2000-10000; The molecular formula of the second plasticizer is R1-(C m H 2m O) n -R2, 2≤m≤6, 2≤m*n≤30, R1 is one of hydroxyl, alkoxy or carboxylate, and R2 is one of hydrogen, alkyl or alkylcarbonyl.
2. The composite plasticizer according to claim 1, characterized in that The mass ratio of the first plasticizer to the second plasticizer is 1:(1-2).
3. A silicon nitride green body, characterized in that: The raw material of the silicon nitride green body includes the composite plasticizer as claimed in claim 1 or 2.
4. The silicon nitride green body according to claim 3, characterized in that: The raw materials of the silicon nitride green body include the following components by weight: 40-55 parts of silicon nitride powder, 1-4 parts of sintering aid, 0.5-3 parts of dispersant, 4-8 parts of binder, 2.5-10 parts of composite plasticizer, 30-40 parts of solvent and 0.2-1 part of defoamer.
5. The silicon nitride green body according to claim 4, characterized in that: The binder comprises polyvinyl butyral with different molecular weights, the weight average molecular weight of the polyvinyl butyral is 50,000-200,000, and the mass proportion of hydroxyl groups in the polyvinyl butyral is 17%-23%.
6. The silicon nitride green body according to claim 4, characterized in that: The solvent includes ethanol and ethyl acetate, and the mass ratio of the ethanol to the ethyl acetate is 4:6 to 7:
3.
7. The silicon nitride green body according to claim 4, characterized in that: The mass proportion of α phase in the silicon nitride powder is greater than 90%, the particle size D50 is less than 1 μm, and the specific surface area is 10-20 m 2 / g.
8. The silicon nitride green body according to claim 4, characterized in that: The sintering aid includes at least one of magnesium oxide and yttrium oxide.
9. The silicon nitride green body according to claim 4, characterized in that: The dispersant includes at least one of polyvinyl pyrrolidone, triethyl phosphate and castor oil.
10. A method for preparing a silicon nitride green body, for preparing the silicon nitride green body as claimed in any one of claims 3 to 9, characterized in that: include: Mixing the raw materials of the silicon nitride green body to obtain silicon nitride slurry; The silicon nitride slurry is tape-casted to obtain the silicon nitride green body.
11. The method for preparing a silicon nitride green body according to claim 10, characterized in that: The raw materials of the silicon nitride green body are mixed to obtain silicon nitride slurry, comprising: Mixing silicon nitride powder, a dispersant, a sintering aid and a portion of a solvent according to a proportion to obtain a first slurry; Mixing a binder, a composite plasticizer, a defoamer and another portion of the solvent according to a certain proportion to obtain a second slurry; The first slurry and the second slurry are mixed to obtain the silicon nitride slurry.
12. A silicon nitride ceramic sheet, characterized in that: The silicon nitride green body is prepared by the silicon nitride green body as described in any one of claims 3 to 9, or is prepared by the method for preparing the silicon nitride green body as described in claim 10 or 11.
Citation Information
Cited By
Composite plasticizer, silicon nitride green body and preparation method therefor, and silicon nitride ceramic piece
WO2026045970A1